PELATIHAN DETEKSI DINI TUMBUH KEMBANG BALITA BAGI PENGELOLA POSYANDU DESA PURWA KERTHI KECAMATAN ABANG KARANGASEM - N.W.A. Utami; I.G.A.S. Darmayani; N.K. Ekawati; L.P. Suariyani (Buletin Udayana Mengabdi, 2023)
The golden period of growth and development is at the age of under five years. Detection of deviations in growth and development can be done at the integrated health post and cadres are the main driver in this detection. Community participation and the capacity of integrated health post’s cadres and managers are still lacking. One of the efforts to increase community participation is capacity training for integrated health post’s cadres and managers. Aims of this training is to increase knowledge of integrated health post’s cadres and managers in Purwa Kerthi Village, Abang District, Karangasem Regency in managing integrated health center and early detection of children under five years growth and development’s deviations. The training used the lecture method, question and answer and case discussions assisted by power point presentations, videos, guidebooks for the growth and development’s implementation at integrated health center and guidebooks for growth and development’s early detection. The participants were 15 people, namely 7 cadres dan 8 managers, including 4 hamlet heads, human development cadre, village staff and village midwife. Before and after the training participants filled out pre--post test questionnaires. The Wilcoxon test were used to analyze data. Knowledge of integrated health center cadres and managers increased after being given training. As an implication, cadres and managers are able to manage integrated health center well, cadres are able to carry out early detection independently and follow up if there are developmental deviations in children under five. Keywords: children, under five years, early detection, integrated health center, cadres, growth and development